What factors influence Generation Y's employee retention in the hospitality industry?: An internal marketing approach. (February 2020) - Frye, William D.; Kang, Soonhwa; Huh, Chang; Lee, Myong Jae (MJ)
Highlights: Individuals from Generation Y are entering in the hospitality job market, but little is known about their intentions to remain in the hospitality business. The purpose of this study is to examine what factors affect a Generation Y employee's intention to remain with a hospitality company with respect to internal marketing factors. Qualtrics, an online survey service company, was used to distribute and collect a self-administered questionnaire survey. A theoretically proposed model was tested using structural equation modeling. The results of this study indicated that "work environment" significantly influence Generation Y employees' job satisfaction, followed by "empowerment, " "pay, " and "relationships with managers, " which in turn, influences "employee commitment" and "intention to remain in hospitality business". Abstract: Individuals from Generation Y are entering into the hospitality job market, but little is known about their intention to remain in the hospitality business. The purpose of this study was to examine what factors affect a Generation Y employee's intention to remain with a hospitality company with respect to internal marketing tactics. Qualtrics, an online survey service company, was used to distribute and collect a self-administered questionnaire survey. A theoretically proposed model was tested using structural equation modeling. The results of this study indicated that "work environment" significantly influence Generation Y employees' job satisfaction, followed by "empowerment, " "pay, " and "relationships with managers, " which in turn, influences "employee commitment" and "intention to remain in hospitality business." The implications of the study are discussed.